Sociological Analysis of New Media's Role in Reducing Afghan Youth Irregular Migration (Salam International Academic Journal, 2025)
This research examines the sociological role of new media in reducing Afghan youth’s inclination toward illegal migration. In light of the increasing prevalence of irregular migration, driven by factors such as insecurity, poverty, unemployment, and limited access to education, this phenomenon poses serious consequences for both Afghan society and destination countries.The study adopts a descriptive-analytical design and employs a mixed-methods approach (qualitative and quantitative) to explore the impact of new media on raising awareness, shaping attitudes, and decreasing the tendency toward illegal migration. The study’s statistical population consists of Afghan citizens, selected through purposive sampling. Data were gathered through questionnaires and semi-structured interviews. Quantitative data were analyzed using SPSS software, while qualitative data were analyzed using thematic analysis and grounded theory through MAXQDA software.The findings indicate that new media, by providing transparent information and authentic accounts of the risks associated with illegal migration, play a significant role in influencing youth attitudes and supporting informed decision-making. However, the spread of misinformation and deceptive advertisements by human traffickers remains a major challenge in this domain.The study recommends that enhancing public awareness through new media, expanding employment and training opportunities, and strengthening legal frameworks and border control mechanisms can collectively contribute to reducing the appeal of illegal migration among youth and managing this crisis more effectively.
Keywords: New Media; Illegal Migration; Afghan Youth; Awareness-Raising; Crisis Management; Social Networks; Human Trafficking; Attitude Change